Smartphones as an extension of the human cyborg: the case of the youth from Aragon (Spain) - Ramos Antón, Rubén (Anàlisi, 2017)
Over the years an idea has been developing that technical advances become the extension of the senses of human beings. A process that has allowed society to evolve. From the relationship between human beings and technology, emerged the concept of the cyborg (Clynes and Kline, 1960), and with a great growth in science fiction that at first referenced the incorporation of exogenous elements to the human being to facilitate their adaptation to extraterrestrial ecosystems. Other definitions that followed (Clarck, 2003) proposed for consideration that the cyborg is the result of the interactions between human beings and technology. Starting from this definition, this article proposes the way that smartphones currently fulfill the function of the nexus between the biological part and the technological part of the human cyborg. For this, through qualitative methodology (life histories), the role of these devices in the lives of eight youth is analyzed. The relevance of investigating youth lies in the role that this collective social plays at the time of incorporating and diffusing elements of novel technology to society. The research is carried out in Aragon, an Spanish Autonomous Community that it continues representing a peripheral territory with little presence at the population level and at the Spanish´s economy. In spite of this and in contrast to what happened in other moments in history, Aragon has approached, even at its most peripheral areas, to the standards of penetration and technological applications of the rest of the world. The research results confirm the important role that smartphones play in the lives of young people as an extension of their senses, in particular, of their brains.